PENGARUH WORKING CAPITAL MANAGEMENT TERHADAP PROFITABILITAS PADA UMKM DI KOTA SURABAYA - Krismi Budi Sienatra; Romauli Nainggolan (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
Working Capital Management had an important role for the success or failure of the company. To achieve the optimal use of working capital management, corporate managers have to accurately control the tradeoffs between profitability and liquidity. The purpose of this study is to examine the relationship between working capital management and business performance at SME in Surabaya. This research is based on primary data on SME in Surabaya which use area sampling technique. The focus area of this ​​research is in West Surabaya. This study was tested using multiple linear regression analysis and the main variables used in account receivable days, inventories days, account payable days, cash conversion cycle as independent variable and profitability as dependent variable. The results showed that inventories days, account payable days, and cash conversion cycles had a significant effect on profitability. The receivable days account has no significant effect on profitability.